2016
DOI: 10.1519/jsc.0000000000001396
|View full text |Cite
|
Sign up to set email alerts
|

Validity of a Wearable Accelerometer Device to Measure Average Acceleration Values During High-Speed Running

Abstract: Alexander, JP, Hopkinson, TL, Wundersitz, DWT, Serpell, BG, Mara, JK, and Ball, NB. Validity of a wearable accelerometer device to measure average acceleration values during high-speed running. J Strength Cond Res 30(11): 3007-3013, 2016-The aim of this study was to determine the validity of an accelerometer to measure average acceleration values during high-speed running. Thirteen subjects performed three sprint efforts over a 40-m distance (n = 39). Acceleration was measured using a 100-Hz triaxial accelerom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…Another approach that has gained acceptance within the area of player tracking is wearable, acceleration-based tracking devices that incorporate microelectromechanical systems (MEMS) gyroscopes, magnetometers, and accelerometers into a single player-worn unit [ 4 ]. The devices utilize tri-axial accelerometers that are not positional based, but movement based (anterior-posterior, medial-lateral, and vertical) [ 5 ], to obtain descriptors of sports activities, such us accelerations, decelerations, jumps, change of direction or other accelerometer-derived measurements [ 6 ]. One such derived measurement is the PlayerLoad™ (Catapult Innovations, Melbourne, Australia), which is used to describe and quantify an athlete’s external workload [ 7 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another approach that has gained acceptance within the area of player tracking is wearable, acceleration-based tracking devices that incorporate microelectromechanical systems (MEMS) gyroscopes, magnetometers, and accelerometers into a single player-worn unit [ 4 ]. The devices utilize tri-axial accelerometers that are not positional based, but movement based (anterior-posterior, medial-lateral, and vertical) [ 5 ], to obtain descriptors of sports activities, such us accelerations, decelerations, jumps, change of direction or other accelerometer-derived measurements [ 6 ]. One such derived measurement is the PlayerLoad™ (Catapult Innovations, Melbourne, Australia), which is used to describe and quantify an athlete’s external workload [ 7 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies with relevance for team sports activities have reported that raw accelerometer data show insufficient accuracy as a measure of impacts during jumping movements or average acceleration during high-speed running (Tran et al, 2010 ; Alexander et al, 2016 ). The authors assumed these discrepancies to result from a lack of gravity-compensation.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the agreement between IMU-based variables and MA system variables mean bias, root mean square error (RMSE; Barnston, 1992 ), 95% limits of agreement (Atkinson and Nevill, 1998 ), Spearman's correlation coefficient and the percentage difference in the mean between criterion (MA) and measurement (CF, KF, LF) expressed as coefficient of variation (CV; Hopkins, 2000 ) were calculated for mean and peak acceleration values in x, y and z-axes (CF, LF, MA) as well as average and peak magnitude of the resulting vector (CF, KF, MA). According to previous research evaluating the relative error of IMU-based acceleration variables a CV ≤5% was considered as small, CV ≥5% and <20% as moderate and CV ≥20% as large (Wundersitz et al, 2015b ; Alexander et al, 2016 ). To approve the acceptable use of MEMS-based sensors in the field a CV <20% was intended (Tran et al, 2010 ; Wundersitz et al, 2015a ).…”
Section: Methodsmentioning
confidence: 99%
“…Screening of the selected papers and the 23 reviews produced 77 additional papers. As a result, 286 studies were identified for inclusion in the systematic review [ 24 , 41 , 43 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , ...…”
Section: Trendsmentioning
confidence: 99%
“…Subject specific models were also developed to estimate CoM velocity during running, based on step rate measures [ 242 ]. The errors entailed in instantaneous velocity estimation can be partially overcome by limiting the velocity analysis to average values in cyclic sports, for example, for each swimming stroke [ 104 , 105 , 106 , 108 , 290 ] turning action [ 192 ], lane [ 63 , 80 , 323 ], running cycle [ 162 , 328 ], or mean velocity in running [ 56 , 160 ]. The average velocity of progression was also obtained from ski IMUs, removing drift and assuming zero-velocity during a portion of the ski thrust phase, in cross-country skiing [ 120 , 237 ] and in uphill mountaineering [ 121 ].…”
Section: Trendsmentioning
confidence: 99%